Between two skies - O'Sullivan, Joanne (Somerville, Massachusetts : Candlewick Press, 2017)
Bayou Perdu, a tiny fishing town way, way down in Plaquemines Parish, Louisiana, is home to sixteen-year-old Evangeline Riley. She has her best friends, Kendra and Danielle; wise, beloved Mamere; and back-to-back titles in the under-sixteen fishing rodeo. But, dearest to her heart, she has the peace that comes only when she takes her skiff out to where there is nothing but sky and air and water and wings. It's a small life, but it is Evangeline's. And then the storm comes. And everything changes. Amid the chaos and pain and destruction comes Tru--a fellow refugee, a budding bluesman, a balm for Evangeline's aching heart. This novel asks compelling questions about class and politics, exile and belonging, and the pain of being cast out of your home. But, perhaps above all, this is a gently woven love story, difficult to put down, impossible to forget.--
Keywords: Teenage girls -- Juvenile fiction; Refugees -- Juvenile fiction; Hurricane Katrina, 2005 -- Juvenile fiction; Teenage girls -- Fiction; Refugees -- Fiction; Love -- Fiction; Plaquemines Parish (La.) -- Juvenile fiction; Hurricane Katrina, 2005 -- Fiction; Bayous -- Fiction; Coming of age -- Fiction; Love -- Fiction; Louisiana -- Fiction; Young adult fiction